Role of donor and recipient sex in platelet transfusion - Stern, Martin; Infanti, Laura; O'Meara, Alix; Sigle, Jörg; Buser, Andreas (Transfusion (Philadelphia, Pa.), 2013)
Background H‐Y proteins are ubiquitously expressed Y chromosome‐encoded minor histocompatibility antigens, which are relevant in the transplantation of hematopoietic stem cells (HSCT) and solid organs. No studies have so far analyzed whether H‐Y incompatibility influences the outcome of platelet (PLT) transfusion. Study Design and Methods We studied the effect of donor and recipient sex on outcome of 9038 single‐donor PLT transfusions. Results Using standard corrected count increment or percent PLT recovery (PPR) calculations, male patients showed inferior recovery rates, irrespective of donor sex. Using an adjusted PPR, which takes into account differences in blood volume between males and females, neither donor nor recipient sex played any role in PLT recovery after transfusion. Similarly, the time to next PLT transfusion was unaffected by both donor and recipient sex. In a subgroup analysis of patients with graft‐versus‐host disease after allogeneic HSCT, male recipients of a female allograft—which may carry anti‐H‐Y T cells and antibodies—had significantly lower time to next PLT transfusion. However, this occurred after both male donor and female donor PLT transfusions, arguing against an involvement of alloreactivity against H‐Y antigens on PLTs. Conclusion This large analysis found no evidence that donor‐recipient sex matching influences the outcome of PLT transfusion.